Changing Gender Gaps in the Timing of First Union Formation and Sexual Initiation in Sub‐Saharan Africa. Issue 2 (20th May 2021) - Batyra, Ewa; Kohler, Hans‐Peter; Furstenberg, Frank F.
Abstract: Gender differences in union formation and sexual initiation in sub‐Saharan Africa remain poorly documented, in large part due to a scarcity of research on the transition to adulthood among men. We adopt a novel perspective on this topic by examining gender gaps in the ages at first union and sex in 24 countries, focusing on measures of central tendency and dispersion. Gender differences in age at first union decreased, driven by postponement among women with relatively late union formation. Yet, due to concurrent persistence of early unions among a sizable portion of women's populations, within‐country heterogeneity in ages at first union increased substantially among women. Thus, although forces responsible for earlier union formation among women than men are weakening, these changes affect population strata unequally. Gender differences in age at first sex decreased to a lesser extent, but in some countries, they disappeared or reversed, uncovering a shift in the relationship between gender and timing of sexual initiation. Changes in union formation and sexual initiation are more heterogeneous across countries among men than women, indicating that these processes among men are more context specific. We show importance of studying men's behavior and exploring heterogeneity in union formation and sexual initiation both within and between populations of women and men.